Self-Controlled Feedback and Learner Impulsivity in Sequential Motor Learning. Issue 1 (February 2019) - Ferreira, Bárbara P.; Malloy-Diniz, Leandro F.; Parma, Juliana O.; Nogueira, Nathálya G. H. M.; Apolinário-Souza, Tércio; Ugrinowitsch, Herbert; Lage, Guilherme M.
Many studies have attributed self-controlled feedback benefits associated with motor learning to learners' greater information processing during practice. However, individual learner characteristics like their impulsivity can also influence how people engage cognitively during learning. We investigated possible dissociations between the types of interaction in self-controlled knowledge of results (KR) and learner impulsivity levels in learning a sequential motor task. Ninety volunteers responded to the self-restraint section of the Barkley deficits in executive functioning scale, and those 60 participants with the highest ( n  = 30) and lowest ( n  = 30) impulsivity scores practiced a motor task involving sequential pressing of four keys in predetermined absolute and relative times. We further divided participants into four experimental groups by assigning the high- and low-impulsivity groups to two forms of KR—self-controlled absolute and yoked. Study results showed no interaction effect between impulsivity and self-controlled KR, and, contrary to expectation, self-controlled KR did not benefit learning, independently of impulsivity. However, low-impulsivity participants performed better than high-impulsivity participants on the absolute dimension of the transfer task, while high-impulsivity learners were better at the relative dimension. Cognitive characteristics of automatic and reflexive processing were expressed by the strategies used to direct attention to relative and absolute task dimensions, respectively. Low-impulsivity learners switched their attention to both dimensions at the end of practice, while high-impulsivity learners did not switch their attention or directed it only to the relative dimension at the end of the practice. These results suggest that the cognitive styles of high- and low-impulsive learners differentially favor learning distinct dimensions of a motor task, regardless of self-controlled KR.